Correlational Analysis between Perception of Parenting Patterns and Resilience in Final Year Students at Syiah Kuala University - Humaira Rizkiya Mardhatillah; Wida Yulia Viridanda; Salman; M. Chalis (STMIK Indonesia Banda Aceh, 2026)
The phenomenon of students' delays in completing their theses is a common issue in higher education, where most students need more time than the ideal study period to graduate. Difficulties in managing academic and psychological pressures during the thesis writing process demonstrate the importance of resilience as an individual's ability to rise above challenges. One factor believed to contribute to resilience is parental parenting patterns perceived by individuals from early development. This study aims to determine the relationship between perceptions of parental parenting patterns and resilience in final year students at Syiah Kuala University. The research method used was a quantitative approach with a correlational design. The instruments used in this study were the Perceived Parenting Style Scale by Divya and Manikandan (2013) for perceived parenting style and the Connor-Davidson resilience Scale by Connor and Davidson (2003) fo resilience. A total of 372 final year students participated as respondents through an accidental sampling technique. The instruments used were the Connor-Davidson Resilience Scale (CD-RISC) and the Perceived Parenting Style Scale, which measure three dimensions of parenting patterns: authoritative, authoritarian, and permissive. The results of the analysis showed that authoritative parenting had a significant positive relationship with resilience (r = 0.846; p < 0.001; R² = 0.716), while authoritarian parenting (r = -0.796; p < 0.001; R² = 0.633) and permissive parenting (r = -0.827; p < 0.001; R² = 0.684) showed a significant negative relationship. These R² values indicate that perceptions of parenting styles explain between 63% to 71% of the variance in student resilience. This study revealed the importance of supportive parenting, especially authoritative parenting, in developing students' psychological resilience so they can complete their studies more effectively.